VD_FINDINFO Décision / 2015 / 264 vom 30. März 2015 - VD Tribunal cantonal (2015)
DÉTENTION PROVISOIRE, PROLONGATION, RISQUE DE RÉCIDIVE, SOUPÇON, PROPORTIONNALITÉ | 221 al. 1 let. c CPP (CH), 222 CPP (CH), 393 al. 1 let. c CPP (CH)